The Nature and Nurture of Callous-Unemotional Traits. (December 2022) - Hyde, Luke W.; Dotterer, Hailey L.
Callous-unemotional (CU) traits, a risk factor for psychopathy, delineate youths with relatively low empathy and guilt, and identify youths with high risk for chronic and severe antisocial behavior (e.g., rule breaking, aggression). We describe work identifying nature and nurture influences on the development of CU traits. Additionally, we clarify the relationship between CU traits and psychopathy, highlight potential misinterpretations of findings on influences of "nature" versus "nurture, " and discuss treatment implications.